2017
DOI: 10.1371/journal.pntd.0005437
|View full text |Cite
|
Sign up to set email alerts
|

Complement inhibition by Sarcoptes scabiei protects Streptococcus pyogenes - An in vitro study to unravel the molecular mechanisms behind the poorly understood predilection of S. pyogenes to infect mite-induced skin lesions

Abstract: BackgroundOn a global scale scabies is one of the most common dermatological conditions, imposing a considerable economic burden on individuals, communities and health systems. There is substantial epidemiological evidence that in tropical regions scabies is often causing pyoderma and subsequently serious illness due to invasion by opportunistic bacteria. The health burden due to complicated scabies causing cellulitis, bacteraemia and sepsis, heart and kidney diseases in resource-poor communities is extreme. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 66 publications
0
44
0
Order By: Relevance
“…It was demonstrated that scabies mites complement inhibitors, such as SMSB4, increase S. pyogenes survival rates in vitro by 2–15 fold . Furthermore, the scabies mite promotes growth of opportunistic pathogens in a porcine model …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that scabies mites complement inhibitors, such as SMSB4, increase S. pyogenes survival rates in vitro by 2–15 fold . Furthermore, the scabies mite promotes growth of opportunistic pathogens in a porcine model …”
Section: Discussionmentioning
confidence: 99%
“…14 It was demonstrated that scabies mites complement inhibitors, such as SMSB4, increase S. pyogenes survival rates in vitro by 2-15 fold. [19][20][21] Furthermore, the scabies mite promotes growth of opportunistic pathogens in a porcine model. 20 As previously mentioned, we surprisingly found only very rare studies about skin bacterial colonizations and superinfections in immunocompetent patients with scabies living in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria have been isolated from skin burrows and mite products (faecal pellets) suggesting that mites could contribute directly to the spread of bacteria. Additionally, it has been shown that complement inhibitors produced by the scabies mite promote the growth and survival of S. pyogenes in vitro, with the suggestion that this may also apply to mite-infested skin in vivo [27]. The presence of scabies is associated with an increased risk of impetigo.…”
Section: Complications Of Scabiesmentioning
confidence: 99%
“…Multiple other uncharacterized antigens with immunomodulatory properties also play a role in reducing the immune response. These may be essential for evasion of host response and parasitism of the epidermis and, thus, open new avenues for vaccine development 44,46,[49][50][51].…”
mentioning
confidence: 99%